Ontology Construction in SaaS Layer of Cloud to Support Multitenancy (Trinity Journal of Management, IT & Media (TJMITM), 2022)
The concept of multitenancy is essential in cloud so as to access variety of services at single go by multiple clients. Several clients access services provided by cloud providers on Pay per usage policy. To ensure relevancy and customization among results on cloud database, ontology is needed to support variability and requirements of tenants. Ontology is the best approach or representation of extracting relevant results from database in Software-as-a-Service (SaaS) layer. The paper deals with customization of SaaS layer by constructing ontology in cloud. The ontology is designed with the help of ontology editor called Hozo related to given domain. The clients on accessing paid services in SaaS layer will get relevant results in context of given domain.
Keywords: Cloud computing; Multitenancy; Ontology; Hozo and SaaS